2016
DOI: 10.25077/jka.v5i1.464
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Indeks Massa Tubuh dengan Kejadian Preeklampsia di RSUP Dr. M. Djamil Padang

Abstract: AbstrakPreeklampsia merupakan penyebab utama kematian maternal selain perdarahan dan infeksi. Penyebab pasti terjadinya preeklampsia belum diketahui, namun terdapat faktor risiko yang mempengaruhi kejadian preeklampsia. Di RSUP Dr. M Djamil Padang terjadi peningkatan kasus preeklampsia setiap tahunnya dari tahun 2008-2012. Tujuan penelitian ini adalah menentukan hubungan antara Indeks Massa Tubuh (IMT) dan kejadian preeklampsia di RSUP Dr. M. Djamil Padang. Penelitian dilakukan di bagian Rekam Medis dengan men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 3 publications
0
6
0
7
Order By: Relevance
“…In addition, those who are observed to be not in preeclampsia are in the normal group, with the score of 22.3 kg/m. The cases of severe and mild preeclampsia at the end of gestational age were discovered to be higher, namely mothers with obesity or overweight [16] .…”
Section: Body Mass Index (Bmi)mentioning
confidence: 99%
“…In addition, those who are observed to be not in preeclampsia are in the normal group, with the score of 22.3 kg/m. The cases of severe and mild preeclampsia at the end of gestational age were discovered to be higher, namely mothers with obesity or overweight [16] .…”
Section: Body Mass Index (Bmi)mentioning
confidence: 99%
“…22 This finding is almost the same with the researcher. Another research carried out by Andriani & Lipoeto (2013) on relationship between BMI and preeclampsia involving 46 cases shows that overweight is highest with proportion of 45% and there is a significant association between BMI and preeclampsia. 23 The proportion of overnourished in nutritional status is dominant in preeclampsia and eclampsia which is 72.3% and 83.4%, respectively.…”
Section: Body Mass Index and Nutritional Statusmentioning
confidence: 96%
“…Another research carried out by Andriani & Lipoeto (2013) on relationship between BMI and preeclampsia involving 46 cases shows that overweight is highest with proportion of 45% and there is a significant association between BMI and preeclampsia. 23 The proportion of overnourished in nutritional status is dominant in preeclampsia and eclampsia which is 72.3% and 83.4%, respectively. A study conducted by Rozikhan (2007) in Dr. Soewondo Kendal hospital by using 200 cases, it found that the proportion of overnourished cases is less than normal nutritional status.…”
Section: Body Mass Index and Nutritional Statusmentioning
confidence: 96%
“…Wanita underweight lebih berisiko mengalami JKM (Jurnal Kebidanan Malahayati),Vol 7,No.2.April 2021, ISSN (Print) 2476-8944 ISSN (Online) 2579-762X, Hal 324-331 preeklampsia dibandingkan dengan yang memiliki berat badan normal. Hal ini dikaitkan dengan adanya anemia berat, serta defisiensi mikronutrien berupa kalsium dan zinc, yang diduga sebagai pemicu terjadinya preeklampsia (Andriani, 2016).…”
Section: Analisa Bivariat Hubungan Pertamahan Berat Badan Ibu Hamil Dengan Angka Kejadian Preeklamsia DI Wilayah Kerja Puskesmas Korpri Kunclassified